E-102 Mechanical Thrombectomy on an Outpatient Basis Is Safe and Feasible. (29th July 2016) - Piotin, M; Redjem, H; Ciccio, G; Smajada, S; Blanc, R
Abstract : Introduction: With the clear Class I, Level of Evidence A indication that thrombectomy for acute stroke is beneficial, the intervention community must, along with the refinement of thrombectomy techniques, work to improve patient triage and workflow. Comprehensive stroke center (CSC) are now at risk of saturation due to augmented patient admission load. Hypothesis: Mechanical thrombectomy (MT) on an outpatient basis may be a solution to avoid congestion in CSC. The question is to determine if MT on an outpatient basis is as safe and effective as conventional hospitalization. Methods: Based on our prospectively gathered database we extracted patients who were admitted for MT for anterior circulation ischemic strokes in our CSC since 2012. Due to practical reasons of organization and workflow, many of these patients were readdressed to the referring stroke centers immediately or within 24 hours after mechanical thrombectomy. We dichotomized patients for which the stay was <24 h (outpatients) and those whose stay was >24 h (inpatients) and compared their characteristics and outcomes. Results: The baseline characteristics of both groups are detailed in Table 1 . Both patient groups were comparable for gender, lateralization of occlusion, intravenous lysis prior to MT, time elapsed from stroke onset to femoral puncture, quality of reperfusion. Outpatients were older but with lower NIHSS at admission, had more frequently isolated MCA than carotid siphon/MCA or tandem occlusions, better DWI-ASPECTS, less often general anesthesia, less procedural complications and better functional outcomes at 3 month. Conclusions: MT on an outpatient basis is safe and feasible. Disclosures: M. Piotin: 2; C; Medtronic, Stryker, Penumbra, Microvention, Balt. H. Redjem: None. G. Ciccio: None. S. Smajada: None. R. Blanc: 2; C; Medtronic, Stryker, Penumbra, Microvention, Balt.